Modeling and simulation of environmental systems : a computation approach - Maurya, Satya Prakash; Yadav, Akhilesh; Singh, R. P. (Boca Raton CRC Press, 2023)
"This book presents an overview of modeling and simulation of environmental systems via diverse research problems and pertinent case studies. It is divided into four parts covering air pollution modeling, sustainable water resources modeling, Internet of Things (IoT) based applications in environmental systems, and future algorithms and conceptual frameworks in environmental systems. Each of the chapter demonstrate how the models, indicators, and ecological processes could be applied directly in the environmental sub-disciplines. It includes range of concepts and case studies focusing on holistic management approach at global level for environmental practitioners. Features: Covers computational approaches as applied to problems of air and water pollution domain. Delivers generic methods of modeling with spatio-temporal analyses using soft computation and programming paradigms. Includes theoretical aspects of environmental processes with their complexity and programmable mathematical approaches. Adopts a realistic approach involving formulas, algorithms, and techniques to establish mathematical models/computations. Provides pathway for real-time implementation of complex modeling problems formulations including case studies. This book is aimed at Researchers, Professionals and Graduate students in Environmental Engineering, Computational Engineering/Computer Science, Modeling/Simulation, Environmental Management, Environmental Modeling and Operations Research"--
Includes bibliographical references and index.
Keywords: Environmental protection; Environmental monitoring; Environmental management; Environmental health; Pollution